Peptide immunoarrays for rationale development of vaccines with enhanced cross-reactivity - Zoë Parker Cates; Antonio Facciuolo; Erin Scruten; Anthony Kusalik; Scott Napper (PLoS ONE, 2025)
Vaccines of enhanced range of protection could help to control newly emerging infectious diseases while providing greater resilience to any subsequent variants. Such “universal vaccines” are an idealized, but unrealized, goal that may benefit from unbiased, high-throughput approaches that define antibody cross-reactivity to enable rational selection of cross-protective epitopes. The priority of this investigation is to establish a pipeline for the identification and preliminary characterization of epitopes with enhanced cross-reactivity. A peptide immunoarray representing the proteomes of SARS-CoV, SARS-CoV-II, and MERS-CoV was applied to characterize spike glycoprotein-specific antibody populations within convalescence serum of SARS-CoV-II infected ferrets. Through two alternate bioinformatic approaches, twenty candidate epitopes were identified and translated into vaccines. Epitopes inducing antibodies with cross-reactivity across naturally occurring versions of spike glycoprotein, including SARS-CoV-II Delta and Omicron variants, as well as antigenically distant SARS-CoV and MERS-CoV, were identified. Working from the assumption that cross-reactivity is prerequisite for cross-protection, this highlights the opportunity and mechanisms by which immunoarrays, coupled with in vitro screening assays, can enable rational selection of epitopes with enhanced potential for cross-protection.